Training workshop with Stakeholders on “Strengthened the Climate Adaptation Strategies in Senegal: role of seeds System Policy for Community Seed Production” 4th and 5th September 2024 - Akinseye, Folorunso; Mbow, Khalifa; Faye, Aliou; Worou, Nadine; Kumar, Shalander (International Livestock Research Institute, 2024)
This report highlights the lessons learned from the workshop held on 4 and 5 September 2024 in Thiès on climate adaptation strategies through community seed systems. The event, organised in collaboration with AICCRA, ICRISAT and other partners, brought together various stakeholders to analyse the shortcomings of seed policies, in particular the lack of integration of local and community seeds, which are essential to the resilience of smallholders in the face of climate challenges. Through presentations, practical work and discussions, avenues were identified for structuring and strengthening these systems, while improving their inclusion in regulatory frameworks. The report proposes concrete recommendations, including training for producers, support for the registration of cooperatives, the adoption of appropriate standards for certifying local seeds, and the creation of a fund dedicated to this type of production. These measures aim to promote resilient and sustainable agriculture in Senegal, by promoting varieties adapted to local climatic conditions and supporting community initiatives.